Passive fit in implant supported dentures [İmplant destekli protezlerde pasif uyum] - (:unkn) unknown (My University, 2012)
The aim of this study was to evaluate the methods used to determine passive fit of implant supported prosthesis and the developed procedures to achive passive fit. The clinical and laboratory procedures employed for framework fabrication are inadequate to provide an absolute passive fit for implant-supported fixed superstructures. However ill-fitting implant frameworks may cause mechanical failures of the prostheses and the implant systems, or biologic complications of the surrounding tissue. Although some prosthetic complications are attributed to the lack of passive fit, its effect on implant success is questionable. Nevertheless, the clinical results of increasing applications of advanced technology to improve framework fit seem promising. This article reviews the clinical significance of passive fit, the factors that affect the final fit of implant supported frameworks and clinical methods for evaluating implant framework fit.
Keywords: Abutment; Implant; Implant supported prosthesis; Passive fit